Pengaruh Inovasi Teknologi dan Kualitas Layanan Dinas Perpustakaan dan Kearsipan Provinsi Bengkulu Terhadap Kepuasan Pemustaka - Gunaidi, Aang; Utama, Sarah Mentari; Agusten, Andre (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2023)
The implementations of information technology in the library field have positive impact not only for librarians as library directors but for visitors as library users.  Bengkulu’s Library Service innovates library services by presenting digital library through an application called "Apo Buek", the discovery of this service aims to improve services to library users. This study designs to determine the effect of technological invention and service quality on Users Satisfaction in Library and Archives Department of Bengkulu. Method in this research used associative exploration and quantitative approach. Questionnaires were distributed to 150 respondents using a purposive sampling technique. The result of the exploration on the t-test showed that the variable technological invention (X1) and service quality (X2) had a positive effect on the user satisfaction variable (Y). This study also proves that contemporaneously there's a significant influence between the variables of technological invention and service quality on users satisfaction. This is grounded on the advised F value of 863.068 and the sig.0.000<0.05. The conclude is the technological invention and service quality carried out by the Library Service of Bengkulu have a veritably strong influence on users satisfaction